Students’ Coping Strategies with Speaking Anxiety in Online Learning Setting - Devia Anggraini; Sidik Indra Nugraha; Yuna Tresna Wahyuna (INTERACTION: Jurnal Pendidikan Bahasa, 2022)
Anxiety is popular topic to discuss. Yet, studies focusing on situations which lead students to feel anxious in online EFL speaking classroom remain scarce. Therefore, this study is aimed to: (1) figure out situation causing students’ anxiety in an EFL speaking classroom; and (2) find out strategies that students use to cope with speaking anxiety. Nine second-year high school students were interviewed to explore the issue. The interview data were analysed using thematic analysis. The result indicated several situations in which students feel anxious when speaking English. These included: speaking in front of big and formal audience, worry of being misunderstood, lack of confidence, and worry of being asked all of sudden. Furthermore, students also used similar strategies to research finding by Kondo & Ying-Ling (2004) even speaking class during online learning setting. There were three strategies mainly used by the students, i.e. preparation, relaxation and positive thinking.